Hypertension Counseling as an Effort to Increase Public Awareness in RT 04-05 Karangbendo - Latiesha Orlaviana; Isnawati Nur Adini; Joya Retno Palupi; Anggun Aulia Kharisma; Aliyyah Az-Zuhrah; Tania Vergawita; Rokhmayanti; Julian Dwi Saptadi (Universitas Veteran Bangun Nusantara, 2025)
Hypertension is one of the most common non-communicable diseases and poses a serious risk of complications if not properly managed. In RT 04 and RT 05, Karangbendo Village, the incidence of hypertension particularly among the elderly is notably high, necessitating promotive and preventive efforts through community service activities. This program aimed to enhance public knowledge regarding hypertension and its prevention through health education and blood pressure screening. The methods employed included educational lectures supported by PowerPoint presentations, distribution of informative leaflets, and assessment of participants’ knowledge using pre- and post-tests. The results indicated a significant improvement in participants’ knowledge, with the proportion of respondents demonstrating good knowledge increasing from 7.1% to 57.1% after the intervention. This community service activity demonstrated that educational interventions can effectively raise public awareness of hypertension and promote healthier lifestyle behaviors. Therefore, similar initiatives should be conducted on a continuous basis, with the support of healthcare professionals, to improve the overall health status of the community. Keywords: Hypertension, Knowledge, Counseling